PENGELOLAAN DAN PENGEMBANGAN PARIWISATA BUDAYA DI KOTA SEMARANG (STUDI KASUS TERHADAP OBYEK WISATA MAEROKOCO) - Fatimah, Nurul (Faculty of Social Science, Universitas Negeri Semarang, 2008)
The Cultural Tourism were one of the Tourism kinds. The number of cultural Tourism increasedevery years in many cities in Indonesia. One of them is Puri Maerokoco in Semarang. Maerokoco asminiature of Central Java Province, on there contains representated of every district or area in CentralJava. The Problem of this research were to take inventory the bad condition, the problem to manage andhow to solve those problem of cultural tourism (Maerokoco). Data collecting technique were doing byobservation, documentation and interview. To analyzing data were doing by description technique. Theresult of the research indicated that Maerokoco, have no many good management. It was cause manyproblems such as, the manager of PRPP, the guardian of Ã¢â‚¬Å“anjunganÃ¢â‚¬Â, district of government and provincegovernment.Exept them, cleanness, security tidiness,and the most important was how to attract muchvisited with variatif promotion doing.Keywords: To develop, to manage, the cultural tourism of Maerokoco